Temperature-dependent photoluminescence emission and Raman scattering from Mo1−xWxS2 monolayers. (27th September 2016) - Chen, Yanfeng; Wen, Wen; Zhu, Yiming; Mao, Nannan; Feng, Qingliang; Zhang, Mei; Hsu, Hung-Pin; Zhang, Jin; Huang, Ying-Sheng; Xie, Liming
Abstract: 2D transition metal dichalcogenide (TMD) alloys with tunable band gaps have recently gained wide interest due to their potential applications in future nanoelectronics and optoelectronics. Here, we report the temperature-dependent photoluminescence (PL) and Raman spectra of Mo1− x W x S2 monolayers with W composition x  = 0, 0.29, 0.53, 0.66 and 1 in the temperature range 93–493 K. We observed a linear temperature dependence of PL emission energy and Raman frequency. The PL intensity is enhanced at high temperature (>393 K). The temperature coefficients are negative for both PL and Raman bands, which may result from anharmonicity, thermal expansion and composition disorder.